Alternative proteins : safety and food security considerations - Bekhit, Alaa El-Din; Riley, William Walter; Hussain, Malik A. (Abington Taylor & Francis, 2023)
"Alternative Proteins: Safety and Food Security Considerations presents up-to-date information on alternative proteins from non-meat sources and examines their nutritional and functional roles as food sources and ingredients. Emphasis is placed on the safety of these novel proteins and an evaluation of their potential contribution to food security. Motivations for novel proteins and restrictions for their use are also discussed. Additionally, this book covers fundamental and recent developments in the production of alternative proteins, and examines safety and consumer acceptability wherever information is available. The sources and processing options for alternative proteins and their impact on final product characteristics are also covered. A collective contribution from international researchers who are active in their field of research and have made significant contributions to the the food sciences, this book is beneficial to any researcher interested in the the food science and safety of alternative proteins"--
Keywords: Food -- Technological innovations; Artificial foods; Wild foods; Food -- Safety measures; Food security; Proteins